TEACHING MATERIALS DEVELOPMENT FOR IMLÂ’ LESSON TO ENHANCE STUDENT’S WRITING SKILLS - Martan Martan; Abdul Hafidz Zaid; Ihwan Mahmudi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
Most of Indonesian students can read Arabic texts, but they cannot write good Arabic according to its rules. This research was aimed to study the characteristics of the teaching materials in Imlâ’ and find out its effectiveness for enhancing writing skill. The research used Research & Development (R&D) methodology, and used four research instruments to collect the data: interviews, questionnaires, tests, and documents for collecting data. In analyzing data, Paired Sample t-Test was used. The procedures started from the literature review, planning, design, validity and experiment to the students. Among the most important results of this research is the presence of teaching materials in the form of a textbook. Its validity is good grade, with a percentage score of 86.4%, meaning that the designed materials can be used with little modification and correction. As for its effectiveness, the researcher studied that Sig. (2-tailed) result is (0,000) < (less than) (0,005). It means that the teaching materials designed for the Imlâ’ are effective to develop the writing skill of students.